2017
DOI: 10.3823/2478
|View full text |Cite
|
Sign up to set email alerts
|

Muscular Variation In The Neck Region With Narrowing Of The Minor And Major Supraclavicular Fossa

Abstract: Background: The sternocleidomastoideus muscle is the most prominent landmarks of the surface anatomy of the neck, separates the anterior part of the neck (anterior triangle) from the posterior part of the neck (posterior triangle). An accessory head of sternocleidomastoideus muscle may cause complications while trying to access vital neurovascular structures that are located in the minor and major supraclavicular fossa. The purpose of this study is to describe an anatomical variation of the sternocleidomastoid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
5
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 0 publications
2
5
1
Order By: Relevance
“…Variations in SCM origin must thus be addressed to avoid complications during surgery. As summarized in Table IV, SCM abnormalities have been reported in many countries around the world including Greece, Brazil, India, Australia, Turkey, Columbia, Pakistan, the US, and Korea (Natsis et al, 2009;Amorim Júnior et al, 2010;Mehta et al, 2012;Raikos et al, 2012;Saxena et al, 2013;Saha et al, 2014;Kim, 2015;Anil et al, 2016;Arquez, 2017;Dupont et al, 2018;Mansoor & Rathore, 2018;Oh et al, 2019). However, most were case reports observed during lessons on gross anatomy for medical or paramedical students, and few systematic studies have been published.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Variations in SCM origin must thus be addressed to avoid complications during surgery. As summarized in Table IV, SCM abnormalities have been reported in many countries around the world including Greece, Brazil, India, Australia, Turkey, Columbia, Pakistan, the US, and Korea (Natsis et al, 2009;Amorim Júnior et al, 2010;Mehta et al, 2012;Raikos et al, 2012;Saxena et al, 2013;Saha et al, 2014;Kim, 2015;Anil et al, 2016;Arquez, 2017;Dupont et al, 2018;Mansoor & Rathore, 2018;Oh et al, 2019). However, most were case reports observed during lessons on gross anatomy for medical or paramedical students, and few systematic studies have been published.…”
Section: Discussionmentioning
confidence: 99%
“…However, most were case reports observed during lessons on gross anatomy for medical or paramedical students, and few systematic studies have been published. SCM variation has been documented in India (27.8 %) and Columbia (11.7 %) (Saha et al, 2014;Arquez, 2017).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…These parapharyngeal tumors can grow into "dumbbell-shaped" tumors, because their growth is directed through the stylomandibular tunnel [14]. Sternocleidomastoideus can be used in several ways by the surgeons who harvest these muscle flaps for reconstructions such as during parotid surgery (parotidectomy), where the Sternocleidomastoideus muscle could serve as an excellent candidate for myocutaneous flap, may cover the surgical defects and possibly preventing Frey's sindrome [15,16] Aktan et al reported a case of double PD in the right side of the face of a 63-year-old male cadaver that merged with each other at a distance of 7 mm before perforating the buccinator muscle. They stated that these ducts were intra-parotid ascending and descending ducts, which did not merge inside the PG as it occurs normally [7].…”
Section: Discussionmentioning
confidence: 99%